Soil microbial sensitivity to temperature remains unchanged despite community compositional shifts along geothermal gradients. (28th September 2021) - Moinet, Gabriel Y. K.; Dhami, Manpreet K.; Hunt, John E.; Podolyan, Anastasija; Liáng, Liyĭn L.; Schipper, Louis A.; Whitehead, David; Nuñez, Jonathan; Nascente, Adriano; Millard, Peter
Abstract: Climate warming may be exacerbated if rising temperatures stimulate losses of soil carbon to the atmosphere. The direction and magnitude of this carbon‐climate feedback are uncertain, largely due to lack of knowledge of the thermal adaptation of the physiology and composition of soil microbial communities. Here, we applied the macromolecular rate theory (MMRT) to describe the temperature response of the microbial decomposition of soil organic matter (SOM) in a natural long‐term warming experiment in a geothermally active area in New Zealand. Our objective was to test whether microbial communities adapt to long‐term warming with a shift in their composition and their temperature response that are consistent with evolutionary theory of trade‐offs between enzyme structure and function. We characterized the microbial community composition (using metabarcoding) and the temperature response of microbial decomposition of SOM (using MMRT) of soils sampled along transects of increasing distance from a geothermally active zone comprising two biomes (a shrubland and a grassland) and sampled at two depths (0–50 and 50–100 mm), such that ambient soil temperature and soil carbon concentration varied widely and independently. We found that the different environments were hosting microbial communities with distinct compositions, with thermophile and thermotolerant genera increasing in relative abundance with increasing ambient temperature. However, the ambient temperature had no detectable influence on the MMRT parameters or the relative temperature sensitivity of decomposition ( Q 10 ). MMRT parameters were, however, strongly correlated with soil carbon concentration and carbon:nitrogen ratio. Our findings suggest that, while long‐term warming selects for warm‐adapted taxa, substrate quality and quantity exert a stronger influence than temperature in selecting for distinct thermal traits. The results have major implications for our understanding of the role of soil microbial processes in the long‐term effects of climate warming on soil carbon dynamics and will help increase confidence in carbon‐climate feedback projections. Abstract : Soils samples along geothermal gradients (at 2, 10 and 30 m from a geothermally active zone) of increasing mean annual temperature (MAT) in two biomes (kanuka stand and grassland) presented shifts in the composition of microbial communities (as shown by the non‐parametric multidimensional scaling (MDS) plots), but similar relative temperature sensitivities ( Q 10 ). The temperature sensitivity was however correlated with the carbon content of soil samples, which varied independently from temperature. The results suggest that while long‐term warming selects for warm‐adapted taxa, substrate quantity exerts a stronger influence than temperature in selecting for distinct thermal traits.